Pengaruh Etos Kerja terhadap Kinerja Guru di Yayasan Amal Islami Almumtaaz Karawang - Aisah, Siti; Suyanto, Suyanto; Zarista, Ramzil Huda (Jurnal Manajemen Pendidikan Islam (MANAPI), 2024)
Teachers play a central role in creating students who have good quality. The problem that occurs is that there are still some teachers who have low work enthusiasm. This can be seen from the way teachers teach which is less innovative, less attention to students and less disciplined so that it affects their performance. This study aims to determine the effect of work ethic on teacher performance at the Al Mumtaaz Karawang. This study was conducted with a quantitative approach using a correlation survey. The sampling technique used random sampling. Data analysis techniques were carried out through simple linear analysis, coefficient of determination and t-test. The results of the study showed that there was a positive and significant influence between work ethic (X) on teacher performance (Y). This can be proven through the t-test with a t-count value of 9.131> from t-table of 2.001. The results of the determination coefficient test (R Square) of 0.586 means that the influence of the independent variable, namely work ethic (X) on the dependent variable, namely teacher performance (Y), is 58.6% and the remaining 41.4% is influenced by other factors. This means that there is a positive and significant influence of work ethic on teacher performance at the Al Mumtaaz Karawang Islamic Charity Foundation.